Lipid content and fatty acid dynamics of female muscle, oocytes and larvae of Prochilodus argenteus (Spix & Agassiz, 1829) - Edenilce de Fátima Ferreira Martins; Larisa Magnone; Martin Bessonart; Deliane Cristina Costa; José Cláudio Epaminondas dos Santos; Nilo Bazolli; Cintia Labussière Nakayama; Ronald Kennedy Luz (Aquaculture Reports, 2020)
This work aimed to determine fatty acid dynamics and lipid composition of female muscle, oocytes, newly hatched larvae (NHL) and first feeding larvae (FFL) of Prochilodus argenteus. Oocytes and NHL had the highest percentages of total lipids. Neutral lipids (NL) and polar lipids (PL) remained constant from oocytes through the larval stages (P < 0.05). Among NL, C18:2n 6 had its highest percentage in muscle (P < 0.05) and C18:3n 3 in muscle and oocytes. The highest percentages of arachidonic acid (AA) were in muscle and FFL. The highest percentages of n-9 and n-6 series were in muscle. The highest values of n-3HUFA were in the larval stages while the highest of n-6HUFA were in muscle and FFL. Percentage of ∑SFA in LN was highest in oocytes, NHL and FFL (P < 0.05) while ∑MUFA was highest in muscle, oocytes and NHL. The highest percentages of ∑PUFA were in muscle and FFL. For PL, however, C18:2n 6 and AA were highest in muscle (P < 0.05) while eicosapentaenoic acid was highest in muscle and oocytes. Percentage of ∑SFA in LP was highest in NHL and lowest in FFL and muscle. The highest percentage of ∑MUFA was in oocytes, NHL and FFL (P < 0.05). The highest percentages for series n-9 were in oocytes and FFL (P < 0.05), while the highest percentages for series n-6 were in muscle and oocytes. The lowest percentage for n-6HUFA was in NHL. The n-3 fatty acids were incorporated into the yolk from body reserves, which were stored prior to vitellogenesis and mobilized to the oocytes. The increase in docosahexaenoic acid reflects the ability of the species to lengthen and desaturate C18:3n 3 yielding n-3HUFA, thus demonstrating the importance of this fatty acid during early development.